Insights into Asparaginase Allergic Responses: Exploring Pharmacogenetic Influences - Daiane Keller Cecconello; Klerize Anecely de Souza Silva; Evelin Cristine Mendonça de Senna; Ciliana Rechenmacher; Liane Esteves Daudt; Mariana Bohns Michalowski (MDPI AG, 2024)
Acute lymphoblastic leukemia represents the most prevalent childhood cancer. Modern chemotherapy has significantly improved outcomes, achieving EFS rates of 80% and OS rates nearing 90% in developed nations, while in developing regions, rates remain below 50%, highlighting disparities, and this difference is due to several factors. Genetic variability plays a role in these drug response disparities, presenting single-nucleotide variations (SNVs). Pharmacogenetic research aims to pinpoint these SNVs early in treatment to predict specific drug responses effectively. This review aims to explore advancements in pharmacogenetics associated with asparaginase (ASNase). ASNase plays a crucial role in the treatment of ALL and is available in three formulations: E. coli, Erwinia, and PEG ASNase. ASNase therapy presents challenges due to adverse effects, like hypersensitivity reactions. Identifying predictive markers for hypersensitivity development beforehand is crucial for optimizing treatments. Several pharmacogenetic studies have investigated the association between SNVs and the risk of hypersensitivity. Key genes include GRIA1, NFATC2, CNTO3, ARHGAP28, MYBBP1A, and HLA. Studies have highlighted associations between SNVs within these genes and hypersensitivity reactions. Notably, most pharmacogenetic investigations of hypersensitivity have focused on patients treated with E. coli, emphasizing the need for broader exploration across different formulations. Future research investigating these variants holds promise for advancing our understanding of ASNase's pharmacogenetics.